English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

13 answers

Put 2 in place of b

2006-12-31 06:01:18 · answer #1 · answered by Anonymous · 0 0

nicely, i'm not particular what you're saying contained in the ingredient area of your question, yet when a= -5 and b= 2, for the equation or 3a-4b, the answer might want to be -23: 3(-5) - 4(2) -15 - 8 =-23

2016-12-01 09:07:49 · answer #2 · answered by fuents 4 · 0 0

ab^3 -a^3b - 3ab^3 + 3a^3b

substitute in the numerical value of b

8a - 2a^3 - 24a + 6a^3

= 4a^3 - 16a

=4(a^3 - 4a)

=4a(a^2 -4)

2006-12-31 06:02:05 · answer #3 · answered by Vinni and beer 7 · 0 0

Um... check behind me... I think this is right. I know you have to substitute b for 2.
(b-a)*(a+b)*ab-(3a*b^3)+(3a^3*b)
(2-a)*(a+2)*2a-(3a*2^3)+(3a^3*2) Rule: substitute property (b=2)
(2a-2a)*2a-(3a*2^3)+(3a^3*2) Rule: distrubute (2-a)(a+2)
(0)*2a-(3a*2^3)+(3a^3*2) Rule: substitute(i think)
0--(3a*2^3)+(3a^3*2) Rule: anything mult. by 0= 0
(-3a*8)+(3a^3*2) Rule: P. Exponents. MD. AS.
-24a+6a^3 Rule: simplify the equation.
Answer: 6a^3-24a
PS. check with your teacher to make sure this is correct. I'm not a teacher!

2006-12-31 06:43:20 · answer #4 · answered by wintertimeisfun 2 · 0 1

Insert the quantity 2 into wherever the variable b is, and simply as best as possible. You do not know the variable a (although you could technically figure that out in higher maths), so simply as best as you are able.

2006-12-31 05:59:08 · answer #5 · answered by Anonymous · 0 0

When the problem gives the value for a variable, such as b = 2, replace each "b" variable with 2. Does the problem give the value for "a?"

2006-12-31 09:44:59 · answer #6 · answered by ♪♥Annie♥♪ 6 · 0 0

(b-a)(a+b)ab-3ab³+3a³b
=(b^2-a^2)ab-3ab³+3a³b
=ab^3-a^3b-3ab^3+3a^3b
=2a^3b-2ab^3
{substitute 2 for b}
=4a^3-16a
=4a(a^2-4)

i hope that this helps

2006-12-31 08:58:35 · answer #7 · answered by Anonymous · 0 0

=(2-a)(2+a)2a - 24a +6a^3
=(4-a^2)2a -24a +6a^3
=8a - 2a^3 -24a + 6a^3
=4a^3 - 16a
=4a(a^2 - 4)
=4a(a-2)(a+2)

2007-01-03 04:15:21 · answer #8 · answered by Como 7 · 0 0

(2-a)(a+2)2a-24a+6a^3 after substituting b for 2
(2-a)(2a^2+4a)-24a+6a^3
4a^2+8a-2a^3-4a^2-24a+6a^3
4a^3-16a
4a(a^2-4)

2006-12-31 07:38:00 · answer #9 · answered by eazylee369 4 · 1 0

Where you see b... replace it with a 2 and simplify...

2006-12-31 06:02:15 · answer #10 · answered by TKD Girl 2 · 1 0

fedest.com, questions and answers